Mobile Query Reformulations - Shokouhi, Milad; Jones, Rosie; Ozertem, Umut; Raghunathan, Karthik; Diaz, Fernando (Proceedings of the ACM International Conference on Research and Development in Information Retrieval (SIGIR2014), 2014)
Users frequently interact with web search systems on their mobile with devices via multiple modalities, including touch and speech. These interaction models are substantially different from the user experience on desktop search. As a result, system designers have new challenges and questions around understanding the intent on these platforms. In this paper, we study the query reformulation patterns in mobile logs. We group query reformulations based on their input method into four categories; text-text, text-voice, voice-text and voice-voice. We discuss the unique characteristics of each of these groups by comparing them against each other and desktop logs. We also compare the distribution of reformulation types (e.g. adding/dropping words) against desktop logs and show that there are new classes of reformulations that are caused by errors in speech recognition. Our results suggest that users do not tend to switch between different input types (e.g. voice and text). Voice to text switches are largely caused by speech recognition errors, and text to voice switches are unlikely to be about the same intent.